Susceptibility of Mice to Vaginal Infection with Chlamydia trachomatis Mouse Pneumonitis Is Dependent on the Age of the Animal - Pal, Sukumar (American Society for Microbiology, 2001)
Mice from three strains, BALB/c (H-2(d)), C3H (H-2(k)), and C57BL/6 (H-2(b)), ranging from 5 to 14 weeks of age, were inoculated intravaginally with different doses of the Chlamydia trachomatis mouse pneumonitis serovar. Vaginal swabs taken at weekly intervals showed that the percentage of animals with positive cultures and the number of inclusion-forming units recovered per mouse were higher in the younger animals. Furthermore, vaginal shedding lasted longer in the young mice than in the older mice. In addition, following mating higher rates of infertility and a decrease in the number of embryos were observed in the infected young mice. In conclusion, susceptibility to a chlamydial vaginal infection is dependent on the age of the mice, with the older animals being more resistant.